Design Options for International Assessment and Review (IAR) and International Consultations and Analysis (ICA) - Ellis, Jane (OECD/IEA Climate Change Expert Group Papers, 2011)
In 2010, the international community took steps to improve the system of reporting and verification under the United Nations Framework Convention on Climate Change (UNFCCC). Parties to the UNFCCC decided at the sixteenth meeting of the Conference of the Parties (COP 16) to enhance reporting for all countries and to conduct "international assessment and review" (IAR) of certain information from developed countries and "international consultations and analysis" (ICA) of biennial update reports from developing countries. This is a step change from the existing reporting and review system - particularly for developing countries, since information from these countries is currently reported on an infrequent basis and is not reviewed. Establishing a system that combines improved reporting with some form of international verification could improve the quality of information available internationally and increase confidence in the integrity of the information reported. This would help to build trust between countries and potentially also increase the level of ambition of mitigation actions. Further decisions need to be made by Parties in order to determine the scope, inputs, process, outputs and frequency of IAR and ICA, as the decisions agreed at COP 16 (known as the "Cancun Agreements") provide limited guidance on these items. This paper outlines key questions to help guide such decisions and provides suggestions for the possible design and function of IAR and ICA. It outlines how they could build on existing review processes under the UNFCCC and draw on lessons from other multilateral review processes. The challenge for the international community will be to ensure that IAR and ICA are useful processes, both nationally and internationally, while minimising the resource requirements needed to implement them